Length-weight relationship and condition factor of the mangrove crab Ucides cordatus (Linnaeus, 1763) (Crustacea, Brachyura, Ucididae) - Pinheiro,Marcelo Antonio Amaro (2009)
The relationship of wet weight (WT) to cephalothorax width (CW) and temporal and seasonal variations in the condition factor were analyzed for each sex of the mangrove crab Ucides cordatus, using specimens collected monthly from September 1998 through September 2000, at Iguape, state of São Paulo. The WT/CW relationship, determined by the regression analysis and the condition factor were evaluated individually, monthly and seasonally, for each sex. The WT/CW relationship indicated isometric growth in males and negative allometric growth in females. Body weight was higher in males than in females of equivalent size and this difference was associated with the males' faster growth and heavier chelipeds. On the other hand, the means for condition factor were always higher for females than for males; the mean condition factor was lower in spring and summer and higher in autumn and winter.